2021
DOI: 10.1177/08295735211055333
|View full text |Cite
|
Sign up to set email alerts
|

Integrative and Theoretical Reviews of Achievement Motivation for School Psychologists: Introduction to the Special Issue

Abstract: A theoretically grounded understanding of achievement motivation appears to be largely overlooked in both initial education programs and ongoing professional development of school psychologists. This is unfortunate because motivation constructs such as perceived control, value, and self-beliefs predict students’ academic performance in a way that complements the variance explained by intelligence tests. This empirical evidence is rooted in long-standing theorizing that motivation constructs hold an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Many researchers have found that students’ achievement motivation is closely and positively correlated with academic performance ( She et al, 2019 ; Gamazo and Martínez-Abad, 2020 ). Various constructs of motivation such as perceived control, values, and self-perception can be used as a supplement to intelligence tests to positively predict the academic performance ( Daniels and Dueck, 2022 ). Achievement motivation of students influences their psychological and behavioral characteristics such as hope of success, coping with failure, persistence in adversity, and willingness to take more challenging courses ( Yeager et al, 2019 ; Kapasi and Pei, 2022 ), which ultimately have an impact on their academic performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Many researchers have found that students’ achievement motivation is closely and positively correlated with academic performance ( She et al, 2019 ; Gamazo and Martínez-Abad, 2020 ). Various constructs of motivation such as perceived control, values, and self-perception can be used as a supplement to intelligence tests to positively predict the academic performance ( Daniels and Dueck, 2022 ). Achievement motivation of students influences their psychological and behavioral characteristics such as hope of success, coping with failure, persistence in adversity, and willingness to take more challenging courses ( Yeager et al, 2019 ; Kapasi and Pei, 2022 ), which ultimately have an impact on their academic performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%